PHASE STRUCTURE, MICROSTRUCTURE AND DIELECTRICS PROPERTIES OF NEW CERAMIC MATERIAL NEAR THE MORPHOTROPIC PHASE BOUNDARY - KRIBAA, O.; BOUTARFAIA, A. (Courrier du Savoir; Vol. 19 (2015): COURRIER DU SAVOIR(Mars), 2015)
ABSTRACT This article investigates the sintering temperature effect on microstructure and dielectric properties of a new ceramic material : Pb0.96Sm0.02Nd0.02[(Zr0.55Ti0.45)1-2x,x(Y2/3 Mo1/3),x( Y2/3Ni1/3)]O3 of perovskite structure , such that x = {0.01,0.03,0.05,0.07,0.1}. In order to study well this system and delimiting the composition close to the morphotropic phase boundary (FMB) in which the tetragonal and rhombohedral phases coexist, we varied the dopants ratio for that various compositions were prepared by conventional solid state process. A thermal treatment was applied to these compositions at different temperatures (1100, 1150, 1180°C), in order to optimize the sintering temperature where the density of ceramics is maximum. We present the preparation and the different stages of the formation of the solid solution. Then we will detail the different techniques of analysis applied to this compound, we begin first by x-ray diffraction, in the following, analysis by scanning electron microscopy (SEM) and finally the study of physical properties (dielectrics). These studies help us to accumulate as much information on these materials. KEYWORDS: Ceramic; Microstructure; dielectrics.